The views of patients with metastatic prostate cancer towards physical activity: a qualitative exploration - Sheill, G.; Guinan, E.; Neill, L. O; Hevey, D.; Hussey, J. (Supportive care in cancer, 2018)
Purpose Patients with metastatic cancer can experience debilitating symptoms, which may influence attitudes towards and engagement in physical activity. This study aimed to examine the attitudes of patients living with metastatic prostate cancer towards physical activity. Materials and methods Semi-structured interviews were completed with male patients living with metastatic prostate cancer. Interviews included eight questions related to patients’ attitudes towards physical activity. Content analysis was conducted on the transcribed interview data. Twenty men with metastatic prostate cancer (mean age 71 ± 8.5 years; body mass index 30.19 ± 5.37 kg/cm 2 ) and associated bone metastases (55% with > 2 regions affected) participated in the study. Results Men’s views towards physical activity were coded into the following major themes: (1) barriers to physical activity, (2) benefits of physical activity, (3) a reduction in physical activity levels post diagnosis and (4) social support for physical activity. Symptoms of metastatic prostate cancer and treatment side effects including pain and fatigue negatively influenced activity participation. In addition, many generic barriers to physical activity were described such as bad weather and a lack of suitable facilities for exercising in rural areas. Conclusion Men living with metastatic prostate cancer have unique needs regarding physical activity related to symptoms of both their cancer and cancer treatment. There is a need to increase prompts that encourage those with metastatic prostate cancer to maintain/increase physical activity levels post diagnosis. Given the individualised needs of this patient group, referral to a cancer exercise specialist should be considered for prescription of tailored physical activity programmes. Trial registration Clinicaltrials.gov NLM Identifier: NCT02453139